Planning and performing yam disease phenotyping 2 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
A seminar presentation on “Planning and Performing Yam Disease Phenotyping” by Dr. Lava Kumar and Dr. Olufisayo Kolade at the International Institute of Tropical Agriculture (IITA)